RECOGNITION OF THE CUSTOMARY LAND LAW IN THE CONSTITUTION OF INDONESIA AND MALAYSIA - Napoh, Datu Bua (Faculty of Law, Universitas Brawijaya, 2015)
Recognition of customary land law is very important for indigenous peoples in their daily lives to protect the existence of the preservation of customary law itself, because this is a traditional lands where they carry out their daily routines and develop their traditional habits which categorized as unique and different from other areas. In Indonesia, the customary land law is recognized as long as it really exists and does not contradict the higher principle and state law. We can see it in article 3 UUPA in 1960, and article 18b paragraph 1945 Constitution of the Republic of Indonesia; while in Malaysia, customary land law is also protected in the Constitution of Malaysia Certificate 134, Original Certificate in 1954. Moreover, the recognition of indigenous land has also been described by the